2023
DOI: 10.3389/fpsyg.2023.1153642
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality-assisted language learning: A follow-up review (2018–2022)

Abstract: Virtual reality (VR) is considered an emerging technology in language education in a previously published review article, which reviews 26 articles on VR-assisted language learning (VRALL) published between 2015 and 2018. VR technology has been developing rapidly and receiving much more attention in language learning, especially in the post-pandemic era. Therefore, following up, this paper tracks the new trends of VRALL by reviewing 38 empirical studies published between 2018 and 2022. The main findings are: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Educational games in VR are engaging due to high immersion levels, but effective feedback mechanisms are crucial for learning (Chen et al, 2023). Recent studies show an expansion in VR-assisted language learning research, exploring cognitive and affective benefits and drawbacks (Hua & Wang, 2023). Overall, VR presents exciting opportunities for fun learning across various educational domains.…”
Section: Resultsmentioning
confidence: 99%
“…Educational games in VR are engaging due to high immersion levels, but effective feedback mechanisms are crucial for learning (Chen et al, 2023). Recent studies show an expansion in VR-assisted language learning research, exploring cognitive and affective benefits and drawbacks (Hua & Wang, 2023). Overall, VR presents exciting opportunities for fun learning across various educational domains.…”
Section: Resultsmentioning
confidence: 99%
“…VR has been shown to improve the learnability of target content by equipping learners with emotional support [ 26 ]; Wang et al, 2021) and lower cognitive loads [ 27 ]. Along the same stream [ 2 ], found that VR had cognitive and affective benefits for language learners [ 28 ]. asserted that VR had been considered by 30 Japanese EFL learners as the most fun and effective tool for language learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, substantial attention has been paid to the applicability of virtual reality (VR) in educational practices [ 1 ]. More than half of academic works on the educational application of VR technologies have focused on high-immersion VR [ 2 ]. One of the most promising benefits that such technologies can contribute to learning is an authentic environment (Chen & Yuen, 2023; [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned articles collectively highlight the potential of VR for English language learning, addressing topics such as gamification [29], benefits of AR and VR for learning outcomes [32], features and educational methods [33], as well as affordances and challenges [34]. VR-assisted language learning has expanded in recent years, and proven to be beneficial in both the cognitive and affective aspects [30,33,35,36]. There were not found, however, studies that address guidelines or considerations to design iVR applications for English learning.…”
Section: Introductionmentioning
confidence: 99%